PRODUCTION AND CHARACTERIZATION OF STILL-DISTILLED RUM - Leite, Marcelo Teixeira; Monteiro, Sandryelle Luciana Bezerra (Seven Editora, 2026)
The global rum market was valued at US$15 billion in 2020 and is projected to reach US$21.5 billion in 2025 at a compound annual growth rate of 5.5% during the period. This growth expectation is due to the global increase in demand for high-quality, intensely flavored rum (Market Data Forecast, 2020). The rum market in Brazil follows the global trend, registering significant growth in consumption in recent years, driven by a public seeking products with more sophisticated and differentiated flavor profiles (Businesscoot, 2020). Thus, rum distilled in copper stills stands out for its fuller-bodied and more complex flavor compared to rum produced in distillation columns, achieving a prominent position in the market. This scenario motivated this study, which aimed to investigate the production and characterization of rum distilled in copper stills, in accordance with current Brazilian legislation. The raw material used was sugarcane molasses. Fermentation was carried out in a fed-batch system using CA-11 yeast, a commercial strain of Saccharomyces cerevisiae. The resulting wine was distilled in a copper still, and rum was produced by diluting the heart fraction of the distillate to 40 ºGL. Physicochemical analyses confirmed that the rum produced meets the requirements established by legislation, demonstrating adequate parameters that guarantee its conformity and quality. Furthermore, the product obtained presented a visual aspect, aroma, and flavor characteristic of excellent beverages, demonstrating that the processes adopted were effective in obtaining a well-crafted distillate.